Child Healthcare and Immunizations in Sub-Saharan Africa During the COVID-19 Pandemic - Buonsenso, Danilo; Cinicola, Bianca; Kallon, Memenatu Ngaima; Iodice, Francesco (Frontiers in Pediatrics, 2020)
Since COVID-19 in the pediatric population is infrequently severe, the indirect costs of the pandemic, related to the measures implemented to deal with the spread of the virus, can be worse than the infection itself. To assess this issue, we evaluated the number of children vaccinated or evaluated for the most common diseases in a poor village in Sierra Leone, showing a worrisome drop in vaccinations performed and children evaluated for acute diseases. Our preliminary findings highlight that support is needed to guarantee basic services to children during COVID-19 pandemic, particularly in poor settings where preventive measures can be life-saving in the long term.